Role Play & Visual Storytelling as an Innovative Solution to Overcome English Grammar Learning for Sixth-Grade Students of SDN 064037 Medan Tembung on Comparative Adjectives and Prepositions Material - Nanda Ramadani; Sri Rahayu Simanullang; Indah Nur Utami Br Simatupang; Putri Olivia Munthe; Siti Sarah Harahap (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to identify and analyze the various challenges experienced by students in understanding two important aspects of English grammar, namely comparative adjectives and prepositions. Based on the results of observations and interviews, it was found that the main obstacle for students lies in the lack of conceptual understanding due to teaching methods that are too theoretical and the minimal use of supporting visual media. In addition, the differences in language structure between Indonesian and English also become obstacles in the learning process. To answer these problems, this study developed and implemented a contextual learning strategy that combines role play and visual storytelling approaches to create an interactive, communicative, and enjoyable learning atmosphere. Through this approach, students not only find it easier to understand the function and use of comparative adjectives and prepositions, but also show significant improvements in active participation, confident when speaking in English, and overall grammar understanding. This study uses a qualitative method with data collection techniques through in-depth interviews and documentation, thus providing a complete picture of the effectiveness of this innovative learning strategy in the context of elementary schools.